TINGKAT KEPUASAN KONSUMEN TERHADAP PELAYANAN â€œBAKSO SOLOâ€ DI KOTA MANADO - Jessy Jane Manasye Mantiri; Melsje Yellie Memah; Grace Adonia Josefina Rumagit (AGRI-SOSIOEKONOMI, 2021)
This study aims to determine the level of customer satisfaction with the service "Bakso Solo". This research was conducted from January to March 2020. The data used in this study are primary data and secondary data. Primary data were obtained through direct interviews with 44 respondents using a questionnaire. The data collection method was carried out using accidental sampling techniques. Data collection regarding customer satisfaction is carried out using a Likert scale measurement. Secondary data obtained from these efforts which are related to this research. The results showed that, the level of consumer satisfaction of the restaurant "Bakso Solo" in the city of Manado was 78.64% or consumers were in the "Satisfied" category.